Do companies walk the talk? Commitments and actions in global supply chain labor standards - Sarah Vandenbroucke; Helen Pluut; Yvonne Erkens; Jaroslaw Kantorowicz (International Journal of Corporate Social Responsibility (JCSR), 2024)
This article examines the efforts towards implementing minimum labor standards in global supply chains through the lens of corporate social responsibility. The adoption of supplier codes of conduct has driven efforts to monitor and enforce standards within these chains. Nonetheless, challenges persist in translating commitment into action, giving rise to gaps in implementation. We address two critical phenomena: corporations' varying internalization of responsibility to implement labor standards, and the translation of these written commitments into actions. Through two distinct studies, we explore how companies 'walk the talk', and navigate the gaps between corporate recognition of responsibility and the establishment of management systems to implement labor standards. The first study demonstrates that a minority of companies are diligent in committing to implement their codes. Only 17% accept a shared responsibility to implement the code, and most companies only refer to audit visits or the termination of supplier contract as mechanisms put in place. The second study does not find conclusive evidence of a correlation between corporate commitments and the evaluation of their corporate sustainability practices in supply chains as evaluated by KnowtheChain. However, results suggest that companies do better when they promote the collaborative approach with suppliers in their implementation efforts.
Keywords: 650; Codes of conduct; Corporate responsibility; Global supply chain; Labor rights